Нові матеріали доби енеоліту Верхньої та Середньої Донщини - Скоробогатов, А. М. (Археологія, 2011)
Аналіз нових джерел доби енеоліту бассейну Верхнього та Середнього Дону з використанням аналогій та дат пам’яток
сусідніх територій, зокрема України, дозволив створити хронологічну шкалу розвитку культур регіону. Дан обзор археологических памятников эпохи энеолита бассейна Верхнего и Среднего Дона так наз. мариупольской
культурноисторической
области с привлечением новых исследований в Воронежской и Липецкой областях.
Анализ материалов с привлечением аналогий из соседних территорий, в частности Украины, а также радиоуглеродных
дат позволил предложить хронологию развития энеолитических культур в Верхнем и Среднем Подонье.
В общих чертах ранний энеолит указанного региона, представленный нижнедонской культурой, датируется
в пределах 6350—5250 ВР. Среднестоговская культура здесь развивалась между 5900 и 4900 ВР, а репинская — с
последней четверти ІV и все ІІІ тыс. до н. э. The Copper Age archaeological sites in the Don River upper and middle regions of so called Mariupol cultural and historic
area are described using the new research in Voronezh and Lipetsk Oblasts.
Analysis of materials using the analogies from the neighbouring territories, particularly from Ukraine, and using the
radiocarbon dates allowed the author to suggest the chronology of the Copper Age cultures development in the Don River
upper and middle regions. In general outline, the Early Copper Age of this region represented by the Nyzhnedonska culture
is dated within the period from 6350 to 5250 BP. Serednyostohivska culture was developing here between 5900 and 4900 BP,
while Repynska culture existed since the last quarter of the 4th millennium and for the whole the 3rd millennium BC.